Structures of Astaxanthin and Their Consequences for Therapeutic Application - Tatas Hardo Panintingjati Brotosudarmo; Leenawaty Limantara; Edi Setiyono; Heriyanto (International Journal of Food Science)
Reactive oxygen species (ROS) are continuously generated as a by-product of normal aerobic metabolism. Elevated ROS formation leads to potential damage of biological structures and is implicated in various diseases. Astaxanthin, a xanthophyll carotenoid, is a secondary metabolite responsible for the red-orange color of a number of marine animals and microorganisms. There is mounting evidence that astaxanthin has powerful antioxidant, anti-inflammatory, and antiapoptotic activities. Hence, its consumption can result in various health benefits, with potential for therapeutic application. Astaxanthin contains both a hydroxyl and a keto group, and this unique structure plays important roles in neutralizing ROS. The molecule quenches harmful singlet oxygen, scavenges peroxyl and hydroxyl radicals and converts them into more stable compounds, prevents the formation of free radicals, and inhibits the autoxidation chain reaction. It also acts as a metal chelator and converts metal prooxidants into harmless molecules. However, like many other carotenoids, astaxanthin is affected by the environmental conditions, e.g., pH, heat, or exposure to light. It is hence susceptible to structural modification, i.e., via isomerization, aggregation, or esterification, which alters its physiochemical properties. Here, we provide a concise overview of the distribution of astaxanthin in tissues, and astaxanthin structures, and their role in tackling singlet oxygen and free radicals. We highlight the effect of structural modification of astaxanthin molecules on the bioavailability and biological activity. These studies suggested that astaxanthin would be a promising dietary supplement for health applications.